Health financing for universal coverage and health system performance : concepts and implications for policy - Kutzin, Joseph (2013)
Examines the definition of health financing for universal coverage as used in the WHOs World health report 2010 to show how UHC embodies specific health system goals and intermediate objectives and, broadly how health financing reforms can influence these.